2022
DOI: 10.1167/iovs.63.5.27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Complex Allele in IMPG2 as a Cause of Adult-Onset Vitelliform Macular Dystrophy

Abstract: Purpose Inherited retinal diseases are a group of clinically and genetically heterogeneous disorders with approximately 270 genes involved. IMPG2 is associated with adult-onset vitelliform macular dystrophy. Here, we investigated two unrelated patients with vitelliform macular dystrophy to identify the underlying genetic cause. Methods Whole-exome sequencing identified a putative causal complex allele consisting of c.3023-15T>A and c.3023G>A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…IMPG2 encodes for the interphotoreceptor matrix proteoglycan 2 protein known to contribute to the organization of the interphotoreceptor matrix. IMPG2 defects are a cause of retinitis pigmentosa and IMPG2-related maculopathy ( 34 36 ). This gene was also a locus identified in the common variant genome-wide association analyses for PS thickness, further highlighting its important role, across both common and rare genomic variants, in PS thickness.…”
Section: Resultsmentioning
confidence: 99%
“…IMPG2 encodes for the interphotoreceptor matrix proteoglycan 2 protein known to contribute to the organization of the interphotoreceptor matrix. IMPG2 defects are a cause of retinitis pigmentosa and IMPG2-related maculopathy ( 34 36 ). This gene was also a locus identified in the common variant genome-wide association analyses for PS thickness, further highlighting its important role, across both common and rare genomic variants, in PS thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The employment of a cell line originating from a tissue or a species different from those of the target gene is not really a matter since the splicing code is highly conserved between closely-related species 19 , as well as cell lines isolated from different organs showed most of the time comparable results when used to perform splicing reporter assays 20 . For instance, the HEK293T cells have been successfully used to analyse hundreds of variants in tens of genes expressed in many different tissues using minigene and midigene assays or FLGA (for examples, see references cited in introduction or 21 23 ). Also, we showed that plasmid contamination can be decreased to an acceptable rate by using DNase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies have highlighted inconsistencies between splicing aberrations detected using midigenes or simpler cellular models, as opposed to more sophisticated models derived from reprogrammed induced pluripotent stem cells, such as photoreceptor precursor cells or retinal organoids. As the genomic context of the complex models closely resembles that of the native retinal environment, these are more representative of the actual splicing process in the retina ( 29 , 32 , 39 , 40 ). These findings point to the limits imposed by the midigene system.…”
Section: Discussionmentioning
confidence: 99%